Willful machines - Floreen, Tim (Simon Pulse, 2015)
In a near-future America, a sentient computer program named Charlotte has turned terrorist, but Lee Fisher, the closeted son of an ultraconservative President, is more concerned with keeping his Secret Service detail from finding out about his developing romance with Nico, the new guy at school, but when the spider-like robots that roam the school halls begin acting even stranger than usual, Lee realizes he is Charlotte's next target.